Democracy and Income Inequality : An Empirical Analysis - Gradstein, Mark; Milanovic, Branko; Ying, Yvonne (World Bank, Washington, DC, 2014)
Standard political economy theories suggest that democratization has a moderating effect on income inequality. But the empirical literature has failed to uncover any such robust relationship. The authors take another look at the issue. The authors argue that prevailing ideology may be an important determinant of inequality and that the democratization effect "works through" ideology. In societies that value equality highly there is less distributional conflict among income groups, so democratization may have only a negligible effect on inequality. But in societies that value equality less, democratization reduces inequality through redistribution as the poor outvote the rich. The authors' cross-country empirical analysis, covering 126 countries in 1960-98, confirms the hypothesis: ideology, as proxied by a country's dominant religion, seems to be related to inequality. In addition, while in Judeo-Christian societies increased democratization appears to lead to lower inequality, in Muslim and Confucian societies it has an insignificant effect. The authors hypothesize that Muslim and Confucian societies rely on informal transfers to reach the desired level of inequality, while Judeo-Christian societies, where family ties are weaker, use political action.